2017
DOI: 10.1212/wnl.0000000000003482
|View full text |Cite
|
Sign up to set email alerts
|

Dementia risk in renal dysfunction

Abstract: Objective: Renal dysfunction has been linked with increased risk for cognitive impairment and dementia, but studies are conflicting. For that reason, the aim of the present systematic review and meta-analysis is to summarize the best available evidence on the prospective association between potential markers of renal dysfunction and development of cognitive impairment or dementia.Methods: Medline, Embase, and Cochrane Database of Systematic Reviews were searched for potential publications until August 1, 2016.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(32 citation statements)
references
References 58 publications
3
23
1
Order By: Relevance
“…We could not show an association between renal damage (determined by either eGFR or UAE) and cognitive performance. This is contradicting with the results of previous studies,10, 11 which might be caused by the small sample size of our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We could not show an association between renal damage (determined by either eGFR or UAE) and cognitive performance. This is contradicting with the results of previous studies,10, 11 which might be caused by the small sample size of our study.…”
Section: Discussioncontrasting
confidence: 99%
“…These imaging markers of cSVD are strongly associated with cognitive function 3, 4, 5, 6. Other types of hypertensive organ damage, such as cardiac and renal damages, have also been linked to lower cognitive function or increased risk of cognitive impairment 7, 8, 9, 10, 11…”
Section: Introductionmentioning
confidence: 99%
“…The findings regarding glucose and creatinine are in accordance with previous literature, with a strong relation between diabetes and a greater risk of dementia. With respect to arginine, a few untargeted metabolomics studies reported an increased serum concentration in cognitively impaired older persons and a lower plasma arginine was one of the most significant metabolic differences in older adults with superior memory performance compared to subjects with normal performance or cognitive disorders .…”
Section: Discussionsupporting
confidence: 92%
“…To account for kidney function and hydration levels [41][42][43], we analyzed the urine concentration of total protein, creatinine, albumin, and the urinary albumin to creatinine ratio (UACR). Individuals with AD showed evidence of kidney function impairment through higher mean concentrations of total protein, albumin, and UACR compared to controls (Table 1), consistent with the higher level of albuminuria recognized with cognitive decline [44][45][46].…”
Section: Resultssupporting
confidence: 55%
“…Distinguishing AD from physiological variations in urine lipids is a challenge, since variation in urine composition can arise from many factors, in particular diet, hydration, time of collection, and kidney disease, for which a number of correction approaches have been used [52]. Further, microalbuminuria is known to occur with cognitive decline [44][45][46]. We chose to collect "spot" urine samples rather than the 24-hour collections that average changes throughout the day, because we intend that any future test in clinical practice must implement a simple collection process.…”
Section: Limitationsmentioning
confidence: 99%